The implementation of case method in English Department of Politeknik Negeri Jember - Asep Samsudin (Journal of English in Academic and Professional Communication, 2022)
Case-based Learning (CBL) is an active learning method that uses the type of case or problem discussion regarding the lesson to be studied. Politeknik Negeri Jember (POLIJE) began to apply the case method practice in practicum sessions, especially in the English Study Program. This research tries to analyse the implementation of the case method in that study program which covers four courses: Speaking for Group Activities, Translation, English for Hotel and Resto, and Grammar. Qualitative research design was used to analyse the data collected through classroom observation. The results revealed: 1) in Speaking for Group Activities course, CBL was implemented thorough classroom discussion that were divided into introduction, main, and closing activities 2) in Translation course, CBL was implemented through question and answer session 3) in English for Hotel and Resto course, CBL was implemented through case study and 4) in Grammar course, CBL was implemented though problem recognition. By revealing the previous findings, it is expected that the description of the implementation of CLB in every course would be well explained.